Impact of Low Hemoglobin on Body Composition, Strength, and Redox Status of Older Hemodialysis Patients Following Resistance Training - da Silva, Victor; Corrêa, Hugo; Neves, Rodrigo; Deus, Lysleine; Reis, Andrea; Souza, Michel; dos Santos, Cláudio; de Castro, Danilo; Honorato, Fernando; Simões, Herbert; Moraes, Milton; Schoenfeld, Brad; et al. (Frontiers in Physiology, 2021)
Introduction: The purpose of this study was to: (i) investigate the effect of six months of resistance training (RT) on body composition, muscle strength, hematological patterns, and redox profile in maintenance hemodialysis (HD) patients, and; (ii) evaluate the effects of baseline concentrations of hemoglobin on the RT response. Methods: One hundred fifty-seven subjects with chronic kidney disease (CKD) were randomly allocated into two groups: Control (CTL, [n = 76]) and RT (n = 81). A first visit was required for anamnesis and anthropometric measurements. Venous blood samples were collected at baseline and after twenty-four weeks of training in all patients for the analysis of clinical and redox balance markers. The RT program spanned six months and consisted of three sets of 8 to 12 repetitions with a rating of perceived exertion between 5-8 for three weekly sessions. Each exercise session was performed in twelve resistance exercises and it least for approximately 40 minutes. Results: The main results demonstrated that RT decreased waist circumference by 3%, and decreased thiobarbituric reactive species (TBARS) by 28%. Moreover, RT increased handgrip strength by 28.4%, fat-free mass by 4.1%, hemoglobin by 5%, iron by 33.4%, glutathione by 121%, and Trolox equivalent antioxidant capacity by 14.2% (p < 0.05). Low hemoglobin concentrations impaired the effect of RT on fat-free mass gain. Conclusion: Six months of RT in HD patients improved clinical parameters, such as hemoglobin, iron, body composition, and redox balance, while low hemoglobin concentration impaired exercise-benefits on fat-free mass in patients with CKD. These findings can contribute to a better clinical application of RT in the maintenance of hemodialysis patients.